2014
DOI: 10.1108/ijchm-12-2012-0244
|View full text |Cite
|
Sign up to set email alerts
|

The effects of emotional labor on frontline employee creativity

Abstract: Purpose – The purpose of this study is to empirically test and extend knowledge of the effects of emotional labor of frontline service employee. Design/methodology/approach – The authors examined the effects of emotional labor (surface acting and deep acting) on frontline employee creativity, as well as the mediating effects of different kinds of job stress (hindrance stress and challenge stress) on the relationship between emotional lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 55 publications
2
61
0
1
Order By: Relevance
“…Although existing research on emotional labor focuses more on attitudes and behaviors of employees in the service field (Geng et al, 2013), there are a very few arguments that emotional labor should be explored on performance outcomes such as creativity and innovation. However, there are also studies investigating the impact of emotional labor on team-level outputs of team innovation (Liu et al, 2008), team performance (Günsel, 2014), and team creativity (Tierney et al,1999).…”
Section: Emotional Labor Results In Project Team Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Although existing research on emotional labor focuses more on attitudes and behaviors of employees in the service field (Geng et al, 2013), there are a very few arguments that emotional labor should be explored on performance outcomes such as creativity and innovation. However, there are also studies investigating the impact of emotional labor on team-level outputs of team innovation (Liu et al, 2008), team performance (Günsel, 2014), and team creativity (Tierney et al,1999).…”
Section: Emotional Labor Results In Project Team Workmentioning
confidence: 99%
“…When employees feel job pressure, they can neglect more difficult and abstract ways of thinking within their job, and also when they are panicked in trying to cope or reduce pressure, they prefer ordinary actions and give up the creative activities (Dyne et al, 2002) When an emotional labor study is conducted, whatever their real emotions, it is stated that the employees can shape their inner emotions as organization expects or can reflect them to the outside as they actually feel. As a result of the studies done, it was found that deep behaviour requires less cognitive resource use, and surface behaviour negatively affects the creativity of the employees; conversely, the deep behaviour positively affects creativity (Geng et al, 2013).Based on these explanations, the following hypotheses were developed; H6: Surface behaviour will have a negative significant influence on team creativity. H7: Deep behaviour will have a positive significant influence on team creativity.…”
Section: 22the Relationship Of Emotional Labor Mechanism and Teammentioning
confidence: 99%
“….g.,Agnihotri, Rapp, Andzulis, & Gabler, 2014;Chang & Teng, 2017;Coelho & Augusto, 2010;Coelho et al, 2011;Geng, Liu, Liu, & Feng, 2014;Gong, Cheung, Wang, & Huang, 2012;Gong, Huang, & Farh, 2009;Hur, Moon, & Rhee, 2016;Madjar & Ortiz- Walters, 2008;Sousa & Coelho, 2011;Van Dyne, Jehn, & Cummings, 2002;Wilder, Collier, & Barnes, 2014) ;Coelho et al, 2011;Stock et al, 2017) 。サー ビス・フロントライン従業員を対象とした既存研究にお いては,サービスの相互作用性という性質によって,サー ビス提供者と顧客との価値共創が重要となっていること に注目し,顧客要因を,創造性を高める先行要因として 扱う研究が蓄積されつつある(e.g.,Coelho et al, 2011;Hur et al, 2016;Madjar & Ortiz-Walters, 2008;Sousa & Coelho, 2011;Wilder et al, 2014) g.,Agnihotri et al, 2014;Wilder et al, 2014) & Ortiz-Walters, 2008) ,顧客へ の信頼(Madjar & Ortiz-Walters, 2008) ,顧客志向(Sousa & Coelho, 2011) ,顧客との関係(Coelho et al, 2011) ,顧 客への共感や期待(Wilder et al, 2014(Wilder et al, )などが挙げられ et al, 2011Sok et al, 2018;Stock et al, …”
unclassified
“…As workplace creativity has been shown to be affected by surface acting (Geng et al, 2014), the current study predicted that reappraisal would partially mediate the association between mindfulness and innovative behaviours by enabling individuals to positively reappraise difficult experiences and thereby increase deep acting and reduce the need for surface acting. However, while reappraisal was significantly correlated with innovative behaviours, it did not mediate the association between innovative behaviours and mindfulness.…”
Section: Dispositional Mindfulness and Innovative Behavioursmentioning
confidence: 99%
“…In other words, emotion regulation strategies such as surface and deep acting may have a bigger influence on creativity when faced with resolving an issue or complaint raised by a customer than when developing and sharing innovative ideas with supervisors and co-workers. Furthermore, developing and implementing new ideas in the types of job roles held by participants in the current study may involve quite different processes than the creative problem solving that was investigated by Geng (2014). More research is needed to elucidate the influence of different emotion regulation strategies on creativity and innovative behaviours, and whether they play any role in the link between mindfulness and innovative behaviours.…”
Section: Dispositional Mindfulness and Innovative Behavioursmentioning
confidence: 99%